Muslim community communication through cross-religious social interaction in the Mardika market Ambon, Moluccas - Sakinah, Nur; Darma, Darma; Sulaeman, Sulaeman; Fitriyani, Andi; Kella, Nurida; Ren'el, Baiti (Jurnal Ilmu Dakwah, 2024)
Purpose – This article aims to map research by elaborating on cross-religious relationships and social interaction communication for the Muslim community in Mardika Market, Ambon City, Maluku.Method – Blumer's theoretical exploration is used with a constructivist paradigm and phenomenological communication method as fundamental references. This review is developed based on input from mardika market management coordinator and identifies current field research obtained qualitatively through several informal conversational interviews and observations of various gaps in social interactions.Results – The article highlights the complexity of cross-religious social interactions impacting intrapersonal, interpersonal, and group communication for the Muslim community in Mardika Market. It begins with understanding cross-religious social interaction relationships and communication events, then finds patterns of communication relationships within the Muslim community.Implications – This article contributes to realize cross-religious harmonization by discussing the search for the meaning of social interactions with the hope of living together peacefully. Strengthening social interactions is very important as it tends to reduce the incidence of cross-religious conflicts. This contribution offers opportunities for social interaction accommodation and ways to avoid cross-religious tensions.Originality/Value – Many published articles focus on cross-religious relationships by detailing the tensions and benefits of cross-religious social interactions, but they are still lacking. However, this study presents the phenomenological communication method and constructivist paradigm to observe the development of communication within the Muslim community engaging in cross-religious social interactions in Mardika Market, Ambon City, Moluccas.***Tujuan – Artikel ini adalah untuk memetakan penelitian dengan mengelaborasi hubungan lintas agama, dan komunikasi interaksi sosial lintas agama bagi komunitas Muslim di pasar Mardika Kota Ambon, Maluku.Metode – Dengan menggunakan penelusuran teoretis dari Blumer dengan paradigma konstruktivis dan metode fenomenologi komunikasi sebagai acuan mendasar. Tinjauan ini dikembangkan berdasarkan masukan dari koordinator pengelola pasar mardika, dan mengidentifikasi kekinian penelitian di lapangan yang diperoleh secara kualitatif melalui beberapa wawacara percakapan informal, dan pengamatan dari berbagai kesenjangan dalam interaksi sosial.Hasil – Artikel menyoroti betapa kompleksnya interaksi sosial lintas agama berdampak pada komunikasi intrapribadi, antarpribadi, dan kelompok bagi komunitas Muslim di pasar mardika. Diawali dengan pemahaman hubungan interaksi sosial lintas agama, dan peristiwa komunikasi, kemudian menemukan pola hubungan komunikasi komunitas Muslim. Implikasi – Kontribusi artikel ini untuk mewujudkan harmonisasi lintas agama melalui pembahasan pencarian makna interaksi sosial dengan harapan dapat hidup bersama secara damai. Penguatan interaksi sosial sangat penting karena cenderung menurunkan insiden konflik lintas agama. Kontribusi ini menawarkan peluang akomodasi interaksi sosial dan cara untuk menghindari ketegangan lintas agama.Orisinalitas/Nilai – Banyak artikel terpublikasi hingga saat ini terfokus pada hubungan lintas agama dengan menguraikan ketegangan dan manfaat interaksi sosial lintas agama masih kurang. Namun kajian ini menyajikan metode fenomenologi komunikasi dan paradigma konstruktivis untuk mengamati pengembangan komunikasi komunitas Muslim melakukan tindakan interaksi sosial lintas agama di pasar Mardika Kota Ambon, Maluku.